Spatial and seasonal pattern of microbial nitrate reduction in coastal sediments in the Vistula River plume area, Gulf of Gdańsk - Benelli, Sara; Bartoli, Marco; Magri, Monia; Brzana, Radosław; Kendzierska, Halina; Styrcz-Olesiak, Kamila; Janas, Urszula (Frontiers in Marine Science, 2024)
Estuaries can remove and/or retain land-derived nitrogen (N) and act as filters buffering N loads to the open sea. The N coastal filter can be seasonally variable depending on water temperature and transported loads, two factors acting in synergy and strongly influenced by climate change. The capacity of sediments to mitigate riverine N loads was investigated at four sites in the Vistula River plume area (Gulf of Gdańsk, Southern Baltic Sea). Samplings were carried out in two contrasting seasons: spring and summer, characterized by different water temperatures and nitrate (NO3-) levels. Inorganic N fluxes, and rates of denitrification and dissimilatory nitrate reduction to ammonium (DNRA) were measured in intact sediment cores by means of dark incubations and 15N-nitrate concentration-series experiments. Sampling sites were selected along a gradient of depth (5 to 24 m), that was also a gradient of sediment organic matter content. In both seasons, denitrification rates increased along with depth and from spring (6.5 ± 7.0 µmol m-2 h-1) to summer (20.4 ± 15.4 µmol m-2 h-1), despite lower NO3- concentrations in summer. In spring, at higher NO3- loading, denitrification was likely limited by low water temperature, and elevated sediment oxygen penetration. Coupled denitrification-nitrification prevailed over denitrification of water column NO3- across all sites and seasons, contributing to over 80% of the total denitrification. Notably, no anammox was detected at the sampling sites. DNRA exhibited low to undetectable rates in spring, especially at the shallowest sites. However, during summer, N recycling via DNRA increased and ranged from 0.7 to 14.9 µmol m-2 h-1. The denitrification efficiency (DE), calculated as the ratio between molecular nitrogen (N2) flux and dissolved inorganic N effluxes from sediments, ranged from 0 to 37% in spring, whereas in summer DE did not exceed 16%. Despite the dominance of denitrification over DNRA, the analyzed sediments acted as weak N buffers under in situ dark conditions. However, concentration-series experiments suggested high potential denitrification capacity, exceeding 400 µmol m-2 h-1, in response to short-term, large riverine inputs of NO3-.